Quality Management in Education – A Comparative Analysis of School Improvement Practices from Luxembourg, Belgium and Croatia - Malgorzata DZIMINSKA (Communications of International Proceedings, 2020)
The article presents a qualitative comparative review of school quality improvement practices from Luxembourg, Belgium and Croatia which are analysed against the key principles of the Total Quality Management: 1) management’s commitment (leadership); 2) focus on the customer and the employee; 3) focus on facts; 4) continuous improvements; 5) everybody’s participation. Interviews with school representatives provided insights which formed the basis for comparing the school quality improvement practices in the three countries and highlighting the key similarities and differences. The analysis contributes to the field of management by revealing strengths and the areas for improvement in the school practices and emphasizing the areas where lessons can be learnt and used to shorten the learning curve on quality improvement based on international experiences.
Keywords: TQM; quality; education; data-based decision making